Intermolecular cooperativity and entanglement network in a miscible PLA/PMMA blend in the presence of nanosilica. (15th January 2016) - Hao, Xiaoqiong; Kaschta, Joachim; Pan, Yamin; Liu, Xianhu; Schubert, Dirk W.
Abstract: Nanosilica filled polylactide (PLA)/Poly(methyl methacrylate) (PMMA) 50/50 blends with varying silica concentrations were prepared by melt mixing. In this work, the effects of silica concentration and the preferential adsorption between silica and the component on the thermo-mechanical and rheological properties of PLA/PMMA blends were systematically investigated. The results of DSC indicate the miscibility of PLA/PMMA/silica nanocomposites in the solid state, and the incorporation of nanosilica does not only increase the glass transition temperature but also extend the broadness of glass transition. Local nanoscale heterogeneities in the miscible blends are proposed due to the self-concentration of the components, and the presence of nanosilica increased the concentration fluctuation and dynamic heterogeneity of the PLA/PMMA blends. A distinct "crater" structure can be observed in the fractured surfaces of the blend nanocomposites. According to the results of SEM and rheological measurements, it was proposed that PLA molecules were selectively adsorbed on the surface of nanosilica, and the preferential adsorption of PLA changed the blend composition in the "crater" structure and the bulk matrix. The phase separation temperature of the filled PLA/PMMA blends was also improved by the incorporation of nanosilica, implying a potential role of nanosilica in improving the phase stability of PLA/PMMA blends. In addition, nanosilica could increase and entanglement density and decrease the entanglement molar mass of the blends in a concentration-dependent manner. Graphical abstract: SEM micrographs of the fractured surfaces of P/P/Si 2 nanocomposites. The specific "crater" structure is highlighted by the red circle (left panel). A schematic diagram illustrating the composition of the "crater" structure in which a preferential adsorption of PLA molecules on the surface of nanosilica aggregates is suggested. Highlights: Preferential adsorption between nanosilica and PLA molecules in the nanocomposites. Nanosilica improves the concentration fluctuation and dynamic heterogeneity in PLA/PMMA blends. The phase separation temperature of PLA/PMMA blends is improved by nanosilica. Molecular entanglement in PLA/PMMA blends is effected by nanosilica due to the selective adsorption.